TRANSMISI NILAI-NILAI KEARIFAN LOKAL TARI KUPANG PADA SISWA DI KABUPATEN SIDOARJO - Niswatin Niswatin; Sugiantoro Sugiantoro (LPPM STKIP PGRI Sidoarjo, 2023)
Culture is obtained from a learning process, not biologically inherited or inherited through genetic elements, so if the local community's wisdom values ​​do not disappear, they will gradually disappear. One way to learn is through research activities. This research, which carries the Kupang dance which is a traditional dance of the Sidoarjo people, aims to reveal and describe the wisdom values ​​of the local Sidoarjo community as a form of actualization of the activities/livelihoods of the Sidoajo people as fishermen in Kupang. As for the urgency and contribution of this research, apart from being an effort to realize and maintain the wisdom values ​​of the local Sidoarjo community, it also reveals the elements or messages contained in an effort to preserve local culture so that it can be better known by the wider community, especially the younger generation. This research is a qualitative descriptive research with data collection techniques through literature studies on the Kupang dance in Sidoarjo Regency, interviews with the local community and the Sidoarjo Regency Arts Service. Data collection techniques using triangulation techniques by combining observation, semi-structured interviews and documentation in the form of texts. The data analysis technique was carried out using model analysis by Miles and Huberman, namely through the stages of data reduction, data display, and verification. The results showed that based on the classification of cultural types, the values ​​of local wisdom in the Kupang dance are the transmission of the values ​​of hard work, mutual cooperation, ethical values ​​(wisdom), values ​​of love, gratitude, creativity, confidence and discipline